Pengaruh Money Attitudes Dan Penggunaan Excessive Social Media Terhadap Pembelian Kompulsif Daring - Akbar, Tri Sanatha Wahyu; Raspati, Galih; Yuningsih, Yuyun Yuniati (Jurnal Ilmiah Manajemen, Bisnis dan Kewirausahaan, 2025)
The rapid development of the digital world and the internet has changed the global marketing landscape from traditional to digital, with social media as the main platform. This study aims to analyze the influence of Money Attitude and Excessive Use of Social Media on Online Compulsive Buying among young people and adults in Sukabumi. This study used a quantitative method with 95 respondents aged 20-40 years, data were collected through questionnaires and analyzed using SPSS 25, including validity and reliability tests, multiple linear regression, t-test, and F-test. The results showed that Money Attitude had a significant positive effect on Online Compulsive Buying. Similarly, Excessive Use of Social Media also had a significant positive effect on Online Compulsive Buying. Simultaneously, Money Attitude and Excessive Use of Social Media significantly influenced Online Compulsive Buying. The implication of this finding is the importance of money attitude education and managing social media use to reduce compulsive buying behavior among young people and adults.